2021
DOI: 10.1021/acs.jpclett.1c03218
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Phonon Anisotropy and Anharmonicity in Exfoliated Natural Black Arsenic

Abstract: Group-VA two-dimensional layered materials in a puckered honeycomb structure exhibit strong in-plane anisotropy and have emerged as new platforms for novel devices. Here, we report on systematic Raman investigations on exfoliated b-As flakes on the A g 1 and A g 2 polarization dependence on their symmetry, excitation wavelength, and flake thickness. The intensity maximums of both phonons are corrected in the b-As armchair direction under 633 nm excitation regardless of the flake thickness upon considering opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…[51] In contrast, Raman intensity of B 2g mode remains unchanged and shows the repeated polarization dependence. [36,52] As shown in Figure 1e, in the parallel configuration, when the two main lattice axes are aligned with the laser polarization, the B 2g mode cannot be detected due to matrix cancellation. Therefore, it allows us to conveniently identify the ZZ or AC directions of b-As flake.…”
Section: Resultsmentioning
confidence: 99%
“…[51] In contrast, Raman intensity of B 2g mode remains unchanged and shows the repeated polarization dependence. [36,52] As shown in Figure 1e, in the parallel configuration, when the two main lattice axes are aligned with the laser polarization, the B 2g mode cannot be detected due to matrix cancellation. Therefore, it allows us to conveniently identify the ZZ or AC directions of b-As flake.…”
Section: Resultsmentioning
confidence: 99%
“…Figure d demonstrates the typical Raman spectrum of the exfoliated b-As nanoflake before the FIB process, which displayed three characteristic phonon modes: the out-of-plane A g 1 and in-plane B 2g and A g 2 . To accurately identify the lattice orientation of b-As, ARPRS and TDPRS were jointly explored. Based on the identical lattice dynamics and group theory with b-P, the ARPRS results showed that the Raman intensity I (B 2g ) of the B 2g mode of the b-As nanoflake varied with the polarization angle θ of the excitation source, leading to the periodic polar plot with 4-fold symmetry. As exhibited in Figure e, the obtained data about its Raman intensity versus polarization angle can be well fitted with I (B 2g ) ∝ cos 2 2θ, where the minimum values imply the AC or ZZ direction of b-As.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the Raman shift of the A g 2 mode presents more significant temperature dependence when the laser polarization is aligned with ZZ (−0.0230 cm −1 /K) than the counterpart AC (−0.0199 cm −1 /K) direction in Figure 1f (more data shown in Figure S1), mostly due to its anisotropic phonon velocity and thus superior thermal conductivity, which is well consistent with literature data. 34 Next, we turn to measure the anisotropic mechanical properties of the prepared b-As nanoribbons along different lattice orientations by using the AFM nanoindentation method and further attempt to extract the elastic modulus through the force−indentation depth curves. As shown in Figure 2a, it is obvious that b-As nanoribbons along the ZZ direction was suspended on the trench of the SiO 2 /Si substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Raman Spectroscopy Measurements: We used an inVia Qontor system (Renishaw, UK) to perform the Raman scattering measurements on the PdTe 2 flakes using 532 nm laser excitation with a spot size smaller than 1 μm and 1800 lines mm À1 grating. [46] The laser power were maintained low enough to avoid a heating impact on the flakes. For TDRS measurements, the samples were put in a controlled stage (Linkam THMS600, UK), where the temperature was taken from 80 to 580 K with a step of 10 K. Initially, the temperature was held at 100 °C with the aid of N 2 gas for 20-30 min to ensure a clean sample and to eliminate water.…”
Section: Methodsmentioning
confidence: 99%